RSM tool life modeling for medium hard turning using PVD tiAIN coated carbide inserts - Noordin Mohd. Yusof, author; The International Conference on Advances in Materials & Processing Technologies (2006: Las Vegas) (Skudai : Universiti Teknologi Malaysia, 2006)
PRZSL